(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Physiotherapists, like many other groups, might be vulnerable to WRMSD in a variety ofsettings. Since research is often conducted in isolated communities or workplaces, there is a dearth ofstudies that assess WRMSD among Saudi physiotherapists. The purpose of this research was toexamine the incidence of WRMSD among Saudi physiotherapists practicing in a variety of clinics andhospitals throughout the country. This research is important because it raises consciousness ofWRMSD among physiotherapists, leading to the implementation of preventative measures and the use ofergonomic tools in a variety of practice settings. The participants in this cross-sectional research filledout online questionnaires that asked them about their personal and professional backgrounds andexposure to potential health risks at work. Purposeful sampling was used to recruit 385physiotherapists. We employed descriptive statistics to assess WRMSD prevalence, and the Chi-Squaretest to identify associations between WRMSD and potential risk variables.